The Accountability of Waqf Managers: Reviewed from Judicial and Accounting Aspects (PSAK NO 412) - Rahman, Taufikur; Farkhani, Farkhani (Badan Wakaf Indonesia, 2025)
Abstract: This research aims to find out the role of the Indonesian Waqf Board in terms of waqf management and dispute resolution, as well as whether BWI Salatiga City has used waqf accounting standards, namely PSAK number 112 concerning waqf accounting in its waqf accounting treatment to realize institutional accountability. Waqf management is based on law number 41 of 2004 concerning waqf. Meanwhile, the accounting standards used as a basis for preparing waqf financial reports are standards issued by the Sharia Accounting Standards Board (DSAS) of the Indonesian Accountants Association (IAI), namely PSAK 112 concerning Waqf Accounting. The research method uses a comparative descriptive method, namely by describing and illustrating the state of the research object and then comparing it with existing standards. Interviews, observation, and documentation obtained research data. The research results show that the Salatiga waqf institution (BWI Salatiga City) has not fully presented its financial reports by generally accepted accounting standards, both PSAK 45 concerning financial reporting of non-profit entities and PSAK 112 concerning waqf accounting. Furthermore, in resolving disputes regarding waqf issues, BWI Salatiga City only acts as a mediator, companion, director, and supervisor, the resolution of waqf problems tends to be left to each party involved. Keywords: Waqf Disputes, Waqf Accounting, Accountability, Waqf Management